2017
DOI: 10.1108/jes-06-2015-0103
|View full text |Cite
|
Sign up to set email alerts
|

Labor mobility across the formal/informal divide in Turkey

Abstract: Purpose This paper, the first one to use individual-level Turkish panel data, examines the labor market transitions in Turkey along the formal/informal employment divide. The purpose of this paper is to contribute to the limited body of empirical evidence available on mobility and informality in the Turkish labor market. Design/methodology/approach Toward this end, the authors use Turkish income and Living Conditions Survey panel data for 2006, 2007, 2008 and 2009 to compute the Markov transition probabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
5
18
1
Order By: Relevance
“…Women are more likely than men to transition from any other state into unfavourable labour market states such as informal employment and informal selfemployment. Tansel and Kan (2017) write that 'our findings clearly support the view that females are significantly disadvantaged in terms of labor mobility' (Tansel and Kan 2017: 32). Education increases the probability of transitions into formal employment and decreases the probability of transitioning into informal employment.…”
Section: Literature Reviewsupporting
confidence: 78%
See 1 more Smart Citation
“…Women are more likely than men to transition from any other state into unfavourable labour market states such as informal employment and informal selfemployment. Tansel and Kan (2017) write that 'our findings clearly support the view that females are significantly disadvantaged in terms of labor mobility' (Tansel and Kan 2017: 32). Education increases the probability of transitions into formal employment and decreases the probability of transitioning into informal employment.…”
Section: Literature Reviewsupporting
confidence: 78%
“…Women entrepreneurs are predominantly concentrated in service activities, while men tend to be owners of companies engaged in manufacturing and construction activities (Bardasi et al 2011). Tansel and Kan (2017) examine transitions between formal employment, informal employment, formal self-employment, and informal self-employment in Turkey. As with other studies, they find that formal employees are the least mobile and the unemployed are the most mobile.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For post‐socialist countries symptoms of segmentation seem to be clearer than in Latin America. Tansel and Kan () also argue for the existence of segmentation and a static employment structure in Turkey.…”
Section: Informality and Mobilitymentioning
confidence: 99%
“…As explained in section 2.1, the study used social security as the measurement criterion for informality. Using the same criterion, Tansel and Acar (2017) analyzed the possibility of transition across formal/informal sectors in Turkey. They found that the formal salaried state is more stable than the other states and that mobility into the formal salaried state is very restricted.…”
Section: Discussionmentioning
confidence: 99%